A grounded theory exploration of how young autistic adults assigned female at Birth (AFAB) make meaning of friendships - Ovadia, Alexa (Department of Psychology, 2026)
Friendships are fundamental to human development and overall well-being. For autistic adults assigned female at birth (AFAB), navigating neurotypical norms and gendered expectations of friendship presents unique challenges, influencing how they understand, value, and experience friendships. Furthermore, autistic AFAB individuals belong to a stigmatised social group, additionally impacting their navigation of friendship. While there is increasing recognition of autistic AFAB adults' experiences, they remain underrepresented in autism due to historical diagnostic discrepancies. This study aims to address this gap by exploring how autistic AFAB individuals make meaning of their friendships, an area that is relatively unexplored. Using a constructivist grounded theory approach, nine semi-structured interviews were conducted with autistic AFAB individuals aged 19 to 28, all of whom had received a clinical autism diagnosis. Social Identity Theory (SIT) informed the analysis, emphasising how group membership as a stigmatised social identity shapes participants' sense of self. The study examined the nuanced ways autistic AFAB young adults assign meaning to friendships by exploring perceptions of friendship, their roles within these relationships, social expectations, and how their autistic identity influences these dynamics. The resulting theory reveals that autistic AFAB individuals construct meaning in their friendships through a dynamic and reciprocal interplay between their experiences of being autistic, social constructs of friendship, and their autistic identity. These elements, although distinct, are interconnected and continuously influence one another. As friendships evolve and individuals undergo personal growth, these processes intersect, shaping and reshaping the meaning and value ascribed to friendships over time. This research contributes to a more inclusive understanding of friendship by centring autistic AFAB individuals' perspectives. It offers critical insights to better support autistic AFAB young adults in fostering meaningful connections and it further challenges prevailing stereotypes about their relational capacities.